2021
DOI: 10.1007/978-3-030-87101-7_8
|View full text |Cite
|
Sign up to set email alerts
|

Walk Extraction Strategies for Node Embeddings with RDF2Vec in Knowledge Graphs

Abstract: As Knowledge Graphs are symbolic constructs, specialized techniques have to be applied in order to make them compatible with data mining techniques. RDF2Vec is an unsupervised technique that can create task-agnostic numerical representations of the nodes in a KG by extending successful language modeling techniques. The original work proposed the Weisfeiler-Lehman kernel to improve the quality of the representations. However, in this work, we show that the Weisfeiler-Lehman kernel does little to improve walk em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In future work, we will implement new parameters to allow these walks. Furthermore, we will incorporate other walk flavors [24], [25].…”
Section: Parameter Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future work, we will implement new parameters to allow these walks. Furthermore, we will incorporate other walk flavors [24], [25].…”
Section: Parameter Analysis and Discussionmentioning
confidence: 99%
“…Additionally, they proposed similarity-oriented and relevance-oriented walk methods and identified the advantages of each method [24]. Steenwinckel et al [25] showed that the WL graph kernel offers little improvements in the context of a single KG with respect to walk embeddings, and proposed five alternative walking strategies.…”
Section: Related Work a Knowledge Graph Embeddings For Rdfmentioning
confidence: 99%
“…In our approach, we choose the RDF2vec [9,10], an unsupervised technique for feature extraction (embeddings), for nodes as well for edges, that has been proposed in several domains (e.g., Semantic Web, Bioinformatics, Social Net-works) and for various purposes (e.g., Semantic Similarity, Link Prediction, Recommendation Systems, Entity Classification) for RDF graphs. Embeddings aim to encode the semantic information mainly for entities; however, in our case, RDF2Vec is applied for properties too.…”
Section: Weight Assignment and Node Selectionmentioning
confidence: 99%
“…• We use RDF2Vec [9,10], a prominent approach for efficiently generating embeddings for the nodes and edges of a KG. We explore several walking strategies for generating embeddings (Random, Anonymous, Walklet, HALK, N-Grams) to identify the optimal one for our problem.…”
Section: Introductionmentioning
confidence: 99%
“…While alternatives to random walks have been proposed as well, the result with those are not yet very conclusive [6,27], which is why we decided to stick to random walks as a sequence extraction technique. In particular, we compare two flavors of random walks:…”
Section: Training Rdf2vec Embedding Vectorsmentioning
confidence: 99%